Negative electrode composite material and preparation method and application thereof
By doping phosphorus, oxygen and nitrogen elements into the carbon material of the negative electrode of the lithium-ion battery and forming a cladding layer on its surface, the problem of insufficient capacity of the negative electrode of the lithium-ion battery is solved, and high specific capacity, long life and excellent magnification are achieved Performance negative electrode composite material.
Patent Information
- Application Number
- CN202411466331.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The graphite specific capacity of the negative electrode of lithium-ion batteries is low, resulting in limited energy density. After the hard carbon is replaced, it is still unable to meet the growing energy density demand.
A carbon material doped with phosphorus (P), oxygen (O) and nitrogen (N) elements is used, and a cladding layer of titanium dioxide and/or alumina is formed on its surface to form a negative electrode composite material.
It improves the specific capacity and electronic conductivity of the negative electrode composite material, extends the cycle life, and optimizes the rate performance, meeting the needs of high energy density and long life.
Smart Images

Figure CN119480952A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to anode composite materials and preparation methods and applications thereof. Background Art
[0002] At present, the energy density of lithium-ion batteries is limited, which is partly attributed to the low specific capacity of graphite commonly used in lithium-ion battery negative electrodes. In order to increase the negative electrode capacity, the industry uses hard carbon to replace graphite as the negative electrode active material, but the capacity of unmodified hard carbon still cannot meet the growing energy density demand. Summary of the invention
[0003] In view of this, the embodiments of the present application provide a negative electrode composite material and a preparation method and application thereof. The negative electrode composite material not only has a higher specific capacity, but also has a longer cycle life and better rate performance.
[0004] A first aspect of an embodiment of the present application provides a negative electrode composite material, comprising a carbon material and a coating layer arranged on the surface thereof; wherein the carbon material is doped with P element, O element and N element, and the material of the coating layer comprises titanium dioxide and / or aluminum oxide.
[0005] Co-doping with phosphorus, oxygen and nitrogen can effectively improve the specific capacity and electronic conductivity of carbon materials. In addition, the coating layer formed by titanium dioxide and / or aluminum oxide can effectively inhibit the expansion of carbon materials during the charge and discharge cycle, thereby extending the cycle life of the negative electrode composite material. Therefore, the above-mentioned negative electrode composite material can have a higher specific capacity, a longer cycle life and better rate performance.
[0006] In some embodiments of the present application, the carbon material is an amorphous carbon nanobelt co-doped with the P element, O element and N element.
[0007] In some embodiments of the present application, the thickness of the coating layer is 5nm-30nm.
[0008] In some embodiments of the present application, based on the mass of the negative electrode composite material, the mass percentage of the carbon material is 28%-40%, the mass percentage of the P element is 4%-5%, the mass percentage of the O element is 36%-45%, the mass percentage of the N element is 4%-5%, and the mass percentage of the Ti element is 14%-19%.
[0009] In some embodiments of the present application, the radial dimension of the negative electrode composite material is 300nm-2000nm.
[0010] A second aspect of the embodiment of the present application provides a method for preparing a negative electrode composite material, comprising:
[0011] Mixing phosphorus element and nitrogen-containing carbon source under a protective atmosphere to prepare a carbon material precursor;
[0012] Forming the coating layer on the surface of the carbon material precursor to obtain a composite material precursor;
[0013] The composite material precursor is heated under a protective atmosphere to obtain the negative electrode composite material.
[0014] The preparation method has simple steps, strong process controllability, high production efficiency and is suitable for large-scale industrial production.
[0015] In some embodiments of the present application, the preparation of the carbon material precursor includes:
[0016] The mixture of the phosphorus element and the nitrogen-containing carbon source is spun to obtain the carbon material precursor in the form of nanofibers; the spinning process includes electrostatic spinning.
[0017] In some embodiments of the present application, the phosphorus element includes red phosphorus with a particle size of 200nm-2000nm, and the nitrogen-containing carbon source includes polyacrylonitrile and / or polyacrylamide.
[0018] In some embodiments of the present application, the mass ratio of the phosphorus element to the carbon source is 1:(5-15).
[0019] In some embodiments of the present application, forming a coating layer on the surface of the nanofiber comprises:
[0020] Titanium dioxide and / or aluminum oxide are deposited on the surface of the nanofibrous carbon material precursor, and the deposition process includes atomic layer deposition.
[0021] In some embodiments of the present application, the heating includes: heating the temperature to 400°C-500°C at a heating rate of 5°C / min-10°C / min and keeping the temperature for 2h-6h.
[0022] The third aspect of the embodiment of the present application provides a negative electrode, including the negative electrode composite material provided in the first aspect of the embodiment of the present application. Due to the use of the negative electrode composite material provided in the embodiment of the present application, the above negative electrode can be used to provide a secondary battery with better rate performance, better cycle performance and higher energy density.
[0023] The fourth aspect of the embodiment of the present application provides a secondary battery, including the negative electrode provided by the third aspect of the embodiment of the present application. Due to the use of the negative electrode provided by the embodiment of the present application, the secondary battery can have better rate performance, better cycle performance and higher energy density.
[0024] The fifth aspect of the embodiment of the present application provides an electric device, including the secondary battery provided in the fourth aspect of the embodiment of the present application. Since the secondary battery provided in the embodiment of the present application can be used for power supply, the electric device has a strong endurance and a certain fast charging capability, and has a good market prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a (Scanning Electron Microscope, SEM) photograph of the composite material precursor prepared in Example 2 of the present application;
[0026] Figure 2A and Figure 2B They are respectively SEM photos and transmission electron microscope (TEM) photos of the negative electrode composite material prepared in Example 2 of the present application;
[0027] Figure 3 This is a rate performance diagram of the button cell of Example 2 of the present application;
[0028] Figure 4 This is a cycle performance diagram of the button cell of Example 2 of the present application at a current density of 0.1 A / g;
[0029] Figure 5 This is a cycle performance diagram of the button battery of Example 2 of the present application at a current density of 0.5 A / g. DETAILED DESCRIPTION
[0030] The embodiment of the present application provides a negative electrode composite material, including a carbon material and a coating layer disposed on the surface thereof; wherein the carbon material is doped with P element, O element and N element, and the material of the coating layer includes titanium dioxide and / or aluminum oxide. In the embodiment of the present application, the carbon material in the negative electrode active material has the ability to extract / insert metal ions (for example, lithium ions). In the embodiment of the present application, X-ray photoelectron spectroscopy (XPS) can be used to characterize the presence of the above-mentioned P element, O element and N element.
[0031] Co-doping with phosphorus, oxygen and nitrogen can expose more active sites of the negative electrode composite material without destroying the adsorption activity of the carbon material, and at the same time increase the specific surface area of the negative electrode composite material, thereby increasing the adsorption amount of metal ions by the negative electrode composite material, and then effectively improving the specific capacity and electronic conductivity of the carbon material. In addition, the coating layer formed by titanium dioxide and / or aluminum oxide can effectively inhibit the expansion of the carbon material during the charge and discharge cycle, thereby extending the cycle life of the negative electrode composite material. Therefore, the above-mentioned negative electrode composite material can have a higher specific capacity, a longer cycle life and better rate performance.
[0032] In some embodiments of the present application, the material of the coating layer is titanium dioxide. Titanium dioxide has good permeability of active ions (eg, lithium ions), which is more conducive to the extraction / embedding of active ions in the negative electrode composite material.
[0033] In some embodiments of the present application, the material of the coating layer includes aluminum oxide. The coating layer formed with the participation of aluminum oxide has a higher density, which is more conducive to limiting the volume expansion of the carbon material during the charge and discharge cycle.
[0034] In some embodiments of the present application, the carbon material is an amorphous carbon nanobelt co-doped with P element, O element and N element. That is, the carbon material is amorphous carbon co-doped with P element, O element and N element, and its morphology is nanobelt-like; amorphous carbon means that the carbon material does not have long-range order. In this way, the negative electrode composite material is easier to prepare; it can also increase the specific surface area of the negative electrode composite material, improve the lithium insertion kinetics of the negative electrode composite material, and thus reduce the risk of negative electrode lithium deposition during battery charging and discharging.
[0035] In some embodiments of the present application, the thickness of the coating layer is 5nm-30nm. Controlling the thickness of the coating layer within the above range can not only provide sufficient binding force to better suppress the expansion of the internal carbon material during the charge and discharge cycle, but also facilitate the penetration of active ions, that is, facilitate the extraction / embedding of active ions in the negative electrode composite material. Specifically, the thickness of the coating layer can be, but is not limited to, 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, 22nm, 25nm, 28nm, 30nm, etc.
[0036] In some embodiments of the present application, based on the mass of the negative electrode composite material, the mass percentage of the carbon material is 28%-40%, the mass percentage of the P element is 4%-5%, the mass percentage of the O element is 36%-45%, the mass percentage of the N element is 4%-5%, and the mass percentage of the Ti element is 14%-19%. By controlling the contents of the above elements within the above ranges, the specific capacity and electronic conductivity of the negative electrode composite material can be maintained at a relatively higher level. In the embodiment of the present application, XPS (X-ray Photoelectron spectroscopy) can be used to test the mass percentage of the above elements in the carbon material. In the embodiment of the present application, the mass proportion of carbon material in the negative electrode composite material can be, for example, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, etc.; the mass proportion of P element in the negative electrode composite material can be, for example, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, etc.; the mass proportion of O element in the negative electrode composite material can be, for example, 36%, 37%, 38%, 39%, 40%, etc. 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc.; the mass proportion of N element in the negative electrode composite material can be, for example, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, etc.; the mass proportion of Ti element in the negative electrode composite material can be, for example, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, etc.
[0037] In some embodiments of the present application, the negative electrode composite material is in the shape of a nanobelt, and the radial dimension of the negative electrode composite material is 300nm-2000nm. By controlling the size of the negative electrode active material within the above range, the length of the extraction / embedding path of the active ions can be controlled within a shorter range, thereby facilitating the rate performance of the negative electrode composite material. Specifically, the radial dimension of the negative electrode composite material can be, for example, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 200nm0, etc.
[0038] The present application also provides a method for preparing a negative electrode composite material, which can be used to prepare the negative electrode composite material provided in the present application. The preparation method includes:
[0039] S01, mixing a phosphorus element and a nitrogen-containing carbon source under a protective atmosphere to prepare a carbon material precursor;
[0040] S02, forming the coating layer on the surface of the carbon material precursor to obtain a composite material precursor;
[0041] S03, heating the composite material precursor under a protective atmosphere to obtain a negative electrode composite material. Under the heating conditions of step S03, the carbon source undergoes a carbonization reaction, and the phosphorus element reacts and is doped into the carbon material. In addition, the titanium dioxide or aluminum oxide in the coating layer can provide an oxygen source, thereby obtaining a carbon material co-doped with phosphorus, oxygen, and nitrogen. In the embodiment of the present application, in step S03, the protective atmosphere can be nitrogen or argon.
[0042] The preparation method has simple steps, strong process controllability, high production efficiency and is suitable for large-scale industrial production.
[0043] In some embodiments of the present application, in step S01, a carbon material precursor is prepared by a spinning process, specifically, comprising:
[0044] After mixing the phosphorus element and the nitrogen-containing carbon source, the obtained mixture is spun to obtain a nanofiber-shaped carbon material precursor, and the spinning process includes electrospinning. In some specific embodiments, in order to obtain a mixture with a suitable viscosity to improve spinnability, a solvent is also added when mixing the phosphorus element and the nitrogen-containing carbon source, and the solid content of the mixture is controlled within the range of 4%-12%.
[0045] In some embodiments of the present application, the phosphorus element includes red phosphorus with a particle size of 200nm-500nm. Using red phosphorus, it is easy to prepare phosphorus-doped carbon materials; controlling the particle size of red phosphorus within the above range is conducive to its uniform dispersion in the mixture, reducing the risk of agglomeration, and having a large specific surface area, which is conducive to doping. Specifically, the particle size of the phosphorus element may not be limited to 200nm, 300nm, 400nm, 500nm, etc. In the embodiments of the present application, a laser particle size analyzer can be used to test the particle size of the phosphorus element.
[0046] In some embodiments of the present application, commercial red phosphorus can be obtained and pretreated to obtain red phosphorus with a target particle size. The pretreatment includes: crushing the commercial red phosphorus, centrifuging the crushed small particles, specifically using a speed of 2000 rpm for the first centrifugation, taking the supernatant and then increasing the speed to 8000 rpm, taking the precipitate, and then vacuum drying to obtain red phosphorus with a particle size of 50nm-500nm.
[0047] In some embodiments of the present application, the nitrogen-containing carbon source includes but is not limited to one or more of polyacrylonitrile (PAN) and / or polyacrylamide.
[0048] In some embodiments of the present application, in step S01, mixing the phosphorus element and the nitrogen-containing carbon source under a protective atmosphere includes:
[0049] The nitrogen-containing carbon source is dispersed in a solvent to obtain a carbon source solution, and then the phosphorus element is dispersed in the carbon source solution under a protective atmosphere, and is fully stirred to obtain a mixture. Specifically, in order to reduce the viscosity of the carbon source solution to accelerate the dispersion of the phosphorus element, the above stirring can be carried out at 20°C-60°C, and the stirring time can be 6h-12h to obtain a uniform mixture. In the embodiment of the present application, the solvent of the carbon source solution can be selected from organic solvents commonly used in the field according to actual production conditions, for example, dimethylacetamide (DMF) and the like.
[0050] In some embodiments of the present application, the mass ratio of phosphorus to nitrogen-containing carbon source is 1: 10. By controlling the mass ratio of the two within the above range, the final doping amount of phosphorus can be within a suitable range.
[0051] In the embodiment of the present application, in step S01, the equipment and process parameters used for electrospinning may be equipment and process parameters known to technicians in the field, and may be adjusted according to actual production conditions. In some embodiments, the voltage range used in electrospinning is 12kV-20kV, the wire speed is 1mL / min-3mL / min, and the distance from the spinning nozzle to the wire collecting device is 25cm-35cm. Among them, the above-mentioned wire collecting device may be a commonly used wire collecting device in the industry, such as a roller. In some embodiments of the present application, the spinning time is 2h-5h. The spinning amount can be controlled by controlling the spinning time.
[0052] In some embodiments of the present application, in step S02, forming a coating layer on the surface of the carbon material precursor includes: depositing titanium dioxide and / or aluminum oxide on the surface of the nanofibrous carbon material precursor. The above-mentioned deposition can be any chemical deposition method familiar to technicians in the field. In some specific embodiments, the above-mentioned deposition process is atomic layer (ALD) deposition. Atomic layer deposition can achieve thickness control at the atomic size level with high flexibility. Since the thickness of the coating layer hardly changes in step S03, in some specific embodiments of the present application, in step S02, the thickness of the coating layer can be controlled within the range of 5nm-30nm. Specifically, the deposition raw material of titanium dioxide can be, for example, Ti(N(CH3)2)4, and the deposition raw material of aluminum oxide can be, for example, Al2O3. Technicians in the field can determine the deposition raw material and deposition conditions according to actual production conditions, and control the thickness of the coating layer by the number of deposition turns.
[0053] In some embodiments of the present application, the heating in step S03 includes: heating to 400°C-500°C at a heating rate of 5°C / min-10°C / min and keeping warm for 2h-6h. That is, the composite precursor is placed in a protective atmosphere, and heated to 400°C-500°C at a heating rate of 5°C / min-10°C / min and kept warm for 2h-6h. Specifically, the insulation temperature of the heating treatment can be but is not limited to 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc. Controlling the insulation temperature within the above range can not only carbonize the nitrogen-containing carbon source to form a carbon material, but also effectively prevent phosphorus atoms, oxygen atoms, and nitrogen atoms from escaping from the system and allowing phosphorus atoms, oxygen atoms, and nitrogen atoms to be doped into the carbon material, and can also prevent the reaction and deterioration of the coating material. In the embodiment of the present application, the above-mentioned insulation time can be, but is not limited to, 2h, 3h, 4h, 5h, 6h, etc., and the insulation time is controlled within the above range, so that the nitrogen-containing carbon source can be fully carbonized, and the production efficiency is high. The embodiment of the present application also provides a negative electrode, including the negative electrode composite material provided in the embodiment of the present application. Due to the negative electrode composite material provided in the embodiment of the present application, the negative electrode can be used to provide a secondary battery with high energy density, excellent cycle performance and good rate performance.
[0054] In some embodiments of the present application, the negative electrode includes a negative electrode current collector and a negative electrode material layer disposed at least on one side surface of the negative electrode current collector, and the negative electrode material layer includes the negative electrode composite material provided in the embodiments of the present application.
[0055] In the embodiment of the present application, the negative electrode active material in the negative electrode material layer may be all the negative electrode composite materials provided in the embodiment of the present application; it may also include other negative electrode active materials known to those skilled in the art, such as silicon-based negative electrode materials, phosphorus-based negative electrode materials (e.g., red phosphorus), etc. The above-mentioned negative electrode active material refers to a substance that can extract / embed active ions.
[0056] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a binder. The conductive agent and binder may be materials suitable for the negative electrode known to those skilled in the art. The mass ratio of the negative electrode active material, the negative electrode composite material, the conductive agent and the binder is not limited, and those skilled in the art may adjust it according to actual application needs.
[0057] In the embodiment of the present application, the negative electrode current collector is used to support the negative electrode material layer, and it can be any negative electrode current collector known to those skilled in the art, such as copper foil.
[0058] In the embodiments of the present application, the negative electrode can be prepared by any process known in the art, and the present application does not limit this. Specifically, taking the wet process as an example:
[0059] The negative electrode composite material provided in the embodiment of the present application, the conductive agent and the binder can be dispersed in a solvent and stirred evenly to obtain a negative electrode slurry; the negative electrode slurry is coated on the surface of the negative electrode collector, and the negative electrode is obtained by drying, rolling and cutting.
[0060] The embodiment of the present application also provides a secondary battery, including the negative electrode provided in the embodiment of the present application. Due to the use of the negative electrode provided in the embodiment of the present application, the secondary battery can have better rate performance, longer service life and higher energy density.
[0061] In the embodiment of the present application, the secondary battery may be a lithium-ion battery or the like.
[0062] In the embodiment of the present application, the secondary battery may be a liquid battery using a liquid electrolyte, a solid-state battery using a solid-state electrolyte, or a semi-solid-state battery.
[0063] In some embodiments of the present application, the secondary battery comprises a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode. In the embodiments of the present application, the positive electrode can be any positive electrode known in the art. The separator can be any separator known in the art.
[0064] The embodiment of the present application also provides an electric device, including the secondary battery provided in the embodiment of the present application. Since the secondary battery provided in the embodiment of the present application can be used for power supply, the electric device has a strong endurance and a certain fast charging capability, and has a good market prospect.
[0065] In some implementations of the present application, the above-mentioned electrical equipment includes but is not limited to vehicles, consumer electronic products, etc. Among them, the above-mentioned vehicles include but are not limited to new energy vehicles, power-assisted bicycles, etc.
[0066] The technical solution of the present application is further explained below in multiple embodiments.
[0067] Example 1
[0068] (1) adding red phosphorus with a particle size of 50-500 nm to a DMF solution of a carbon source (specifically polyacrylonitrile), stirring at 60° C. for 12 h to obtain a mixture; in the mixture, the mass ratio of red phosphorus to polyacrylonitrile is 1:10.
[0069] (2) The mixture was transferred to a needle tube and connected to an electrospinning machine for electrospinning at a voltage of 16 kV and a spinning speed of 1 mL / min. The distance from the spinning nozzle to the collecting device was 25 cm, and the spinning time was 4 h, thereby obtaining a nanofiber-shaped carbon material precursor.
[0070] (3) A titanium dioxide coating layer was deposited on the surface of the carbon material precursor prepared above by an atomic deposition process. The thickness of the coating layer was 15 nm, thereby obtaining a composite material precursor.
[0071] (4) The composite material precursor was placed in a tubular furnace, heated to 450°C at a rate of 10°C / min under a nitrogen atmosphere and kept at that temperature for 4 h to obtain a negative electrode composite material.
[0072] Example 2
[0073] The difference from Example 1 is that: (2) the mixture is transferred to a needle tube, connected to an electrospinning machine for electrospinning, the voltage is 16 kV, the spinning speed is 1.5 mL / min. The distance from the spinning nozzle to the collecting device is 25 cm, the spinning time is 4 h, and a nanofiber-shaped carbon material precursor is obtained.
[0074] (3) A titanium dioxide coating layer was deposited on the surface of the carbon material precursor prepared above by an atomic deposition process. The thickness of the coating layer was 15 nm, thereby obtaining a composite material precursor.
[0075] (4) The composite material precursor was placed in a tubular furnace, heated to 400° C. at a rate of 10° C. / min under a nitrogen atmosphere and kept at that temperature for 0.6 h to obtain a negative electrode composite material.
[0076] Example 3
[0077] The difference from Example 1 is that: (2) the mixture is transferred to a needle tube, connected to an electrospinning machine for electrospinning, the voltage is 16 kV, the spinning speed is 1.5 mL / min. The distance from the spinning nozzle to the collecting device is 25 cm, the spinning time is 4 h, and a nanofiber-shaped carbon material precursor is obtained.
[0078] (3) A titanium dioxide coating layer was deposited on the surface of the carbon material precursor prepared above by an atomic deposition process. The thickness of the coating layer was 25 nm, thereby obtaining a composite material precursor.
[0079] (4) The composite material precursor was placed in a tubular furnace, heated to 450°C at a rate of 10°C / min under a nitrogen atmosphere and kept at that temperature for 0.6 h to obtain a negative electrode composite material.
[0080] Example 4
[0081] (1) adding red phosphorus with a particle size of 50-500 nm to a DMF solution of a carbon source (specifically polyacrylonitrile), stirring at 60° C. for 12 h to obtain a mixture; in the mixture, the mass ratio of red phosphorus to polyacrylonitrile is 1:10.
[0082] (2) The mixture was transferred to a needle tube and connected to an electrospinning machine for electrospinning at a voltage of 16 kV and a spinning speed of 1 mL / min. The distance from the spinning nozzle to the collecting device was 25 cm, and the spinning time was 4 h, thereby obtaining a nanofiber-shaped carbon material precursor.
[0083] (3) An aluminum oxide coating layer was deposited on the surface of the carbon material precursor prepared above by an atomic deposition process. The thickness of the coating layer was 15 nm, thereby obtaining a composite material precursor.
[0084] (4) The composite material precursor was placed in a tubular furnace, heated to 450°C at a rate of 10°C / min under a nitrogen atmosphere and kept at that temperature for 4 h to obtain a negative electrode composite material.
[0085] Comparative Example 1
[0086] (1) adding red phosphorus with a particle size of 50-500 nm to a DMF solution of a carbon source (specifically polyacrylonitrile), stirring at 60° C. for 12 h to obtain a mixture; in the mixture, the mass ratio of red phosphorus to polyacrylonitrile is 1:10.
[0087] (2) The mixture was transferred to a needle tube and connected to an electrospinning machine for electrospinning at a voltage of 16 kV and a spinning speed of 1 mL / min. The distance from the spinning nozzle to the collecting device was 25 cm, and the spinning time was 4 h, thereby obtaining a nanofiber-shaped carbon material precursor.
[0088] (3) The carbon material precursor was placed in a tubular furnace, heated to 400° C. at a rate of 10° C. / min under a nitrogen atmosphere and kept at that temperature for 0.6 h to obtain a negative electrode composite material.
[0089] Comparative Example 2
[0090] (1) A DMF solution of a carbon source (specifically polyacrylonitrile) is stirred at 60° C. for 12 h to obtain a mixture; in the mixture, the mass ratio of red phosphorus to polyacrylonitrile is 1:10.
[0091] (2) The mixture was transferred to a needle tube and connected to an electrospinning machine for electrospinning at a voltage of 16 kV and a spinning speed of 1 mL / min. The distance from the spinning nozzle to the collecting device was 25 cm, and the spinning time was 4 h, thereby obtaining a nanofiber-shaped carbon material precursor.
[0092] (3) A titanium dioxide coating layer was deposited on the surface of the carbon material precursor prepared above by an atomic deposition process. The thickness of the coating layer was 15 nm, thereby obtaining a composite material precursor.
[0093] (4) The composite material precursor was placed in a tubular furnace, heated to 450°C at a rate of 10°C / min under a nitrogen atmosphere and kept at that temperature for 4 h to obtain a negative electrode composite material.
[0094] Performance Testing
[0095] (1) Morphology test: The composite material precursors prepared in each embodiment and comparative example were placed under SEM to observe their morphology, and the negative electrode composite materials prepared in each embodiment and comparative example were placed under SEM and TEM to observe. Among them, the SEM photo of the composite material precursor prepared in Example 2 is as follows: Figure 1 As shown, the SEM and TEM images of the prepared negative electrode composite material are respectively as shown in Figure 2A and Figure 2B As shown; it has been observed that the negative electrode composite materials prepared in each embodiment are in the shape of nanobelts, and the radial dimensions are distributed in the range of 300nm-2000nm.
[0096] (2) Elemental analysis test: The negative electrode composite materials prepared in each embodiment and comparative example were subjected to XPS test. The results are summarized in Table 1.
[0097] (3) Electrochemical performance test
[0098] ① Preparation of test battery: The negative electrode active material, conductive agent (multi-walled carbon nanotubes) and binder (carboxymethyl cellulose solution with a concentration of 2wt.%) prepared in each embodiment and comparative example are dispersed in a solvent (specifically deionized water) at a mass ratio of 7:2:1, and stirred evenly to obtain a negative electrode slurry; the negative electrode slurry is coated on the surface of the copper foil using a 50μm scraper, and after drying at 100°C for 12h, it is taken out and cut into discs to obtain a negative electrode; in a glove box (filled with argon, water and oxygen less than 0.05ppm), the above-mentioned negative electrode and the counter electrode (lithium metal sheet) are assembled into a 2032 button battery, and a commercial 1M LiPF6 ethylene carbonate and diethyl carbonate (1:1) electrolyte is injected.
[0099] ②First discharge capacity test: At a constant temperature of 25°C, the button cells of each embodiment and comparative example were charged at 0.1Ag -1 The current is discharged to 0.005V, and then 0.1Ag -1 Charge at constant current to 1.5V and record the first discharge capacity of the battery.
[0100] ③ Cyclic performance test: at a constant temperature of 25°C, with 0.1Ag -1 The current is discharged to 0.005V, and then 0.1Ag -1 Constant current charging to 1.5V; stand for 10min; 0.1C constant current discharge to 0.005V, that is, 1 cycle. Repeat this step, and test the battery capacity and capacity retention rate after 80 cycles. Capacity retention rate (%) = discharge capacity of the nth cycle / discharge capacity of the first cycle × 100%. The results are summarized in Table 2.
[0101] ④ Rate performance test: At a constant temperature of 25°C, at 0.1A g -1 Constant current discharge to 0.005V, constant current charge to 1.5V cut-off; 0.2A g -1 Constant current discharge to 0.005V, constant current charge to 1.5V cut-off; 0.5A g -1 Constant current discharge to 0.005V, constant current charge to 1.5V cut-off; 1A g -1 The constant current discharge is to 0.005V, and the constant current charge is to 1.5V and cut off.
[0102] Figure 3 This is a rate performance diagram of the button cell of Example 2; Figure 4 This is a cycle performance diagram of the button cell of Example 2 at a current density of 0.1 A / g; Figure 5 This is a cycle performance diagram of the button cell of Example 2 at a current density of 0.5 A / g.
[0103] Table 1
[0104] Case C Ti O N P Example 1 39.60% 14.55% 36.83% 4.62% 4.40% Example 2 38.42% 15.10% 37.56% 4.53% 4.39% Example 3 28.63% 18.3% 44.70% 4.24% 4.13% Example 4 37.63% 15.20% 38.14% 4.71% 4.32% Comparative Example 1 77.26% 0% 8.54% 7.23% 6.97% Comparative Example 2 41.39% 15.67% 37.92% 5.02% 0%
[0105] Table 2
[0106]
[0107]
[0108] It can be seen from the data in Table 1 and Table 2 that the negative electrode composite material provided in the embodiments of the present application can simultaneously improve the cycle performance and rate performance of the secondary battery, and can also maintain the initial discharge capacity of the battery at a relatively high level.
[0109] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A negative electrode composite material, characterized in that: It includes a carbon material and a coating layer arranged on the surface of the carbon material; The carbon material is doped with P element, O element and N element, and the material of the coating layer includes titanium dioxide and / or aluminum oxide.
2. The negative electrode composite material according to claim 1, characterized in that: The carbon material is an amorphous carbon nanobelt co-doped with the P element, the O element and the N element.
3. The negative electrode composite material according to claim 1, characterized in that: The coating layer has a thickness of 5nm-30nm.
4. The negative electrode composite material according to any one of claims 1 to 3, characterized in that: Based on the mass of the negative electrode composite material, the mass percentage of the carbon material is 28%-40%, the mass percentage of the P element is 4%-5%, the mass percentage of the O element is 36%-45%, the mass percentage of the N element is 4%-5%, and the mass percentage of the Ti element is 14%-19%.
5. The negative electrode composite material according to claim 2, characterized in that: The radial dimension of the negative electrode composite material is 300nm-2000nm.
6. The method for preparing the negative electrode composite material according to any one of claims 1 to 5, characterized in that: include: Mixing phosphorus element and nitrogen-containing carbon source under a protective atmosphere to prepare a carbon material precursor; Forming the coating layer on the surface of the carbon material precursor to obtain a composite material precursor; The composite material precursor is heated under a protective atmosphere to obtain the negative electrode composite material.
7. The preparation method according to claim 6, characterized in that: The preparation of the carbon material precursor comprises: The mixture of the phosphorus element and the nitrogen-containing carbon source is spun to obtain the carbon material precursor in the form of nanofibers; the spinning process includes electrostatic spinning.
8. The preparation method according to claim 6 or 7, characterized in that: The phosphorus element includes red phosphorus with a particle size of 200nm-2000nm, and the nitrogen-containing carbon source includes polyacrylonitrile and / or polyacrylamide.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The mass ratio of the phosphorus element to the carbon source is 1:(5-15).
10. The preparation method according to any one of claims 6 to 9, characterized in that: The forming of a coating layer on the surface of the nanofiber comprises: Titanium dioxide and / or aluminum oxide are deposited on the surface of the nanofibrous carbon material precursor, and the deposition process includes atomic layer deposition.
11. The preparation method according to any one of claims 6 to 10, characterized in that: The heating comprises: heating to 400°C-500°C at a heating rate of 5°C / min-10°C / min and keeping the temperature for 2h-6h.
12. A negative electrode, characterized in that: The negative electrode composite material comprises the negative electrode composite material as described in any one of claims 1 to 5.
13. A secondary battery, characterized in that: Comprising the negative electrode as claimed in claim 12.
14. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 13.
Citation Information
Patent Citations
Preparation method of P, N-doped porous carbon fiber-TiO2 lithium ion battery negative electrode material
CN112447957A
Porous silicon / titanium dioxide / graphene composite material as well as preparation method and application thereof
CN113346060A
Nitrogen and fluorine co-doped titanium dioxide / carbon micro-sphere material, preparation method thereof and application of nitrogen and fluorine co-doped titanium dioxide / carbon micro-sphere material in sodium-ion battery
CN113937257A
Long-circulation lithium battery negative electrode material as well as preparation method and application thereof
CN116072831A
Composite hard carbon material, preparation method and application thereof, and battery
CN116454273A
Cited By
Silicon-based negative electrode material and preparation method and application thereof
CN120432516A